Predictors of repeated-sprint ability in elite female hockey players - Bishop, D.; Lawrence, S.; Spencer, M. (Journal of Science and Medicine in Sport, 2003)
The ability to maintain maximal power over a series of sprints may depend, in part, on the resynthesis of PCr and the buffering of hydrogen ions (H+). As a result, repeated-sprint ability may be related to VO2peak and changes in plasma pH. Fourteen elite female field-hockey players (Mean +/- SD body mass: 61.1 +/- 5.9 kg and VO2pea: 55.7 +/- 3.2 mL x kg(-1) x min(-1)) participated in this investigation. Tests consisted of a repeated-sprint ability test (5 x 6-s all-out sprints every 30 s) and a VO2peak test. Capillary and venous blood was sampled before and after the 5 x 6-s cycle test for the determination of lactate concentration and pH. There were no significant correlations between VO2peak (mL x kg(-1) x min(-1)) and total work (J.kg(-1); r = 0.35), or power decrement (r = 0.30) during the repeated-sprint ability test. There was, however, a significant correlation between power decrement and change in plasma [H+] (r = 0.66; P < 0.05). The results of this study show that in a homogenous group of elite, team-sport athletes, VO2peak (mL x kg(-1) x min(-1)) is not a strong predictor of repeated-sprint ability. However, in this group, there is a significant correlation between change in plasma [H+] and repeated-sprint ability.